To tell you the truth : a novel - Macmillan, Gilly (William Morrow, an imprint of HarperCollinsPublishers, 2020)
The disappearance of her fawningly dependent husband catapults best-selling mystery writer Lucy Harper into dark memories about her brother who went missing under suspicious circumstances thirty years earlier.